Fractionated semen collection as a diagnostic tool for reproductive pathologies in stallions - Oliveira, S. N. [UNESP]; de Araujo, E. A.B. [UNESP]; Silva, L. F.M.C. [UNESP]; Hayashi, R. M. [UNESP]; Merenda, V. R.; Papa, F. O. [UNESP] (Wiley, 2021)
The alterations found in the ejaculate of stallions, obtained through fractionated semen collection, may be used as a diagnostic tool for identifying the origin of the pathology. The occurrence of seminal vesiculitis, lacerations and urethral rents, bulbourethritis, and prostatitis may be accurately identified through the use of fractionated semen collection. However, because findings can at times be vague or misleading, if possible, one should pursue complimentary examinations for a definitive diagnosis. The clinical findings obtained through the fractionated semen collection should be reasonably interpreted by the veterinarian. Thus, we aimed to illustrate the findings obtained through fractionated semen collection in stallions with ejaculate alterations, which may allow the identification of the origin of pathological alterations.
Keywords: abnormalities contamination; haemospermia; horse; pathologies; pyospermia